International Financial Statistics, November 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This November 2015 issue of International Financial Statistics is a standard source of statistics on all aspects of international and domestic finance. This annual publication provides detailed data on transactions in revenue, expense, net acquisition of assets and liabilities, other economic flows, and balances of assets and liabilities of general government and its subsectors. The data are compiled according to the framework of the 2014 Government Finance Statistics Manual, which provides for several summary measures of government fiscal performance. The country tables, euro area tables, and world tables provide measures of effective exchange rates, compiled by the IMF's Research Department, Strategy, Policy, and Review Department, Statistics Department, and area departments. The General Resources Account (GRA) resources consist of the currencies of Fund member countries, SDRs, and gold. Borrowings are regarded as a temporary source of funds. In order to supplement its quota resources, the IMF has the authority to borrow the currency of any member from any source with the consent of the issuer.